2023
DOI: 10.1039/d2ra08281k
|View full text |Cite
|
Sign up to set email alerts
|

Visible light antibacterial potential of cement mortar incorporating Cu-ZnO/g-C3N4 nanocomposites

Abstract: A hybrid Cu-ZnO/g-C3N4 nanocomposite was synthesized and introduced to fabricate photocatalytic cement mortar whose bactericidal activity was investigated under visible light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
4
0
2
Order By: Relevance
“…By releasing it from ZnO, Zn 2+ can destroy the cell membrane leading to the inhibition of cell proliferation due to the denaturation of proteins and the disruption of the cellular energy mechanism by disturbing the electron transport. Although there are numerous reports in the literature attributing the potential antibacterial effect of Zn after catalysis, it was demonstrated that a strong antibacterial effect was also obtained in dark conditions [60]. The opinion of some researchers is that the antibacterial effect of Zn does not increase with the rise in Zn 2+ concentration.…”
Section: Zinc Oxide (Zno)mentioning
confidence: 99%
“…By releasing it from ZnO, Zn 2+ can destroy the cell membrane leading to the inhibition of cell proliferation due to the denaturation of proteins and the disruption of the cellular energy mechanism by disturbing the electron transport. Although there are numerous reports in the literature attributing the potential antibacterial effect of Zn after catalysis, it was demonstrated that a strong antibacterial effect was also obtained in dark conditions [60]. The opinion of some researchers is that the antibacterial effect of Zn does not increase with the rise in Zn 2+ concentration.…”
Section: Zinc Oxide (Zno)mentioning
confidence: 99%
“…Correspondingly, a small shift in absorption peaks of Z 0.5 C 0.5 CN (approximately at 3320 cm − 1 , 1650 cm − 1 , 1250 and 813 cm − 1 ) towards the lower wavenumber is observed compared to that of pristine g-C 3 N 4 peaks. That alteration in peaks identi es the strong chemical interaction rather than simple physical interaction between the components of the heterostructure catalyst [47]. The Point of Zero Charge (PZC) analysis was applied to surface charge of photocatalyst surface as a function of pH, which in turn to investigate the mode of interaction of EBT onto photocatalyst surface.…”
Section: Ftir Spectroscopy Analysesmentioning
confidence: 99%
“…如, 在 Cu 掺杂 ZnO 材料传感 NO 2 研究方面, Patil 等 [19] 采用湿化学方法合成了纳米棒传感材料; Cu 掺杂浓度改变六边形 ZnO 晶体结构和材料表面形貌, 其器件可实现低温(120~220 ℃)下对 NO 2 气敏性能快 速响应和高选择性检测. Salunkhe 和合作者 [13] 采用共沉 淀方法制备了 Cu 掺杂 ZnO 薄膜器件; 在 3%原子比掺 杂时和 200 ℃工作温度时, 可对 188 mg/m³ NO 2 实现 326%的高响应性, 响应和回复时间分别为 17 和 158 s. Cu 掺杂 ZnO 敏感材料还应用于 NH 3 [20][21] 、丙酮 [22] 、 H 2 S [23] 、CO [24] 、H 2 [25] 等传感研究, 同时还在光催化、抗 菌等领域有广泛应用 [26][27][28][29] .…”
Section: 引言unclassified
“…尤其是引入金属杂原子和材料复合的情 况下, 材料的结构表征则更加困难. 因此, 在本工作中, [12][13][14][19][20][21][22][23][24][25][26][28][29] . ZOC 中包括两类相邻 Cu• , 而 Cu 的氧化 态则介于一价和二价之间, 与实验的 X 射线光电子能谱 (XPS)表征相一致 [24] .…”
Section: 引言unclassified